Impact of External Shocks on Tobacco and Tobacco Related Products Company Performance Using Stata Statistical Softwar - Donnyanto Adrian Limadinata (Eduvest - Journal of Universal Studies, 2026)
This research investigates the impact of external shocks, particularly changes in excise tax rates and the COVID-19 pandemic, on the financial performance of tobacco companies in Indonesia, specifically PT Hanjaya Mandala Sampoerna, Tbk. (HMSP). Using a quantitative approach, time-series data from 2018 to 2025 were analyzed, focusing on key financial indicators such as net revenue, cost of goods sold, and selling expenses. The study reveals that increases in excise tax significantly affect the company’s cost structure and tax liabilities, while the COVID-19 pandemic led to a decrease in net revenue but had minimal impact on tax obligations. The findings indicate that, despite fiscal pressures, tobacco companies have adapted through strategic pricing and cost-optimization strategies to mitigate the impact of these external shocks. This study contributes to understanding the effectiveness of fiscal policy in the tobacco industry and provides empirical evidence of how companies can adjust their strategies to maintain financial resilience amid regulatory and market disruptions.